PENERAPAN STRATEGI PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV C SD NEGERI 163 PEKANBARU - Meli Zulhairani Zulhairani; Zariul Antosa Antosa; Lismasil ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem underlying this study is the low student learning outcomes in social studies class IV C Elementary School 163 Pekanbaru . This research shaped Classroom Action Research ( CAR), which aims to improve student learning outcomes IPS Elementary School fourth grade C 163 Pekanbaru through the strategy map concept . Map concept as defined by Martin concrete illustrations that indicate how a single concept - linked kekonsep other concepts in the same category . By mastering the concept of the students acquire a broad knowledge . This study was conducted from April to May The subjects were students of class IV C Elementary School 163 Pekanbaru the number of students as many as 37 people . Data collection instruments in this research is the teacher and student activity sheets and achievement test . This study analyzed data on student learning outcomes obtained from daily tests I and II . In the daily test I obtained average is 67.56 students . In the second daily test scores obtained by the students as much as 74.72 . Daily test results of students in comparison with a base score before the study is 60.54 . Judging from the base score percentages improving student learning outcomes at the first daily test is 11 % and the daily test II is 23 % . Teacher and student activity data obtained by observation sheet teachers and students . Teacher activity increased at each cycle , the average activity of teachers in the first cycle is 75 % and increased in the second cycle into 90.62 % . While the student activity observed with the student activity sheet also increased at each cycle , the average score of student activity cycle 1 is 57.5 % increase in the second cycle is 82.5 % . From the above analysis of the research data it is known that the application of learning strategies concept maps can enhance students' learning outcomes IPS Elementary School fourth grade C 163 Pekanbaru . Thus the research hypothesis is proven .Keywords : Strategy Map concept . Learning Outcomes IPS .